Energy minimization methods in computer vision and pattern recognition : 11th International Conference, EMMCVPR 2017, Venice, Italy, October 30-November 1, 2017, Revised Selected Papers /: 11th International Conference, EMMCVPR 2017, Venice, Italy, October 30-November 1, 2017, Revised Selected Papers. (2018) - Unknown
No abstract available